Pengembangan Usaha Pembuatan Sabun Cuci Piring dengan Menggunakan Teknologi Alat Mixing - Nursamsu Nursamsu; Afrah Junita; Hasby Hasby (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The purpose of the service activities carried out by the service team is to provide training socialization to PKK Gampong Sungai Pauh Pusaka mothers, West Langsa District, Langsa City to make dish soap using mixing tool technology. This activity will later be beneficial for the PKK Gampong Sungai Pauh Pusaka group. This activity is also expected to be able to create business opportunities for PKK members and the community. Activities are carried out through 5 (five) stages which include (1) Survey; (2) delivery of mixing equipment; (3) Making dish soap and (4) Product packaging; (5) Monitoring and Evaluation. The training in making dish soap improved the skills of PKK women in producing lots and quality of dish soap using mixing equipment technology. The results of the evaluation and monitoring show that this service activity shows that the PKK group continues the production of dish soap as an effort to earn the group's business and is used for daily needs.